SOME PROPERTIES OF SPATIAL QUANTILES - Trzpiot, Grażyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Conditional quantiles are required in various economic, biomedical or industrial problems. Lack of objective basis for ordering multivariate observations is a major problem in extending the notion of quantiles or conditional quantiles (also called regression quantiles) in a multidimensional setting. We present characterisations of the spatial quantiles and the corresponding estimators. Nonparametric inference is very naturally quantile-based, and in recent years various notions of multivariate quantiles the spatial quantile function for whose sample version have been recalled.